A REVIEW OF GENOME ORGANIZATION, EVOLUTION, TRANSMISSION, CIRCULATION, AND CLINICAL MANIFESTATION OF MONKEYPOX VIRUS - Stefka Krumova; Daniel Ivanov; Iva Christova (Problems of Infectious and Parasitic Diseases)
Mpox is an illness caused by the monkeypox virus (MPXV, genus Orthopoxvirus), which infects animals and humans. Genetically, there are two MPXV clades: The Central (1) and West (2), with two reported subclades for each. MPXV can be transmitted between animals, from animals to humans, and humans to humans. Since May 2022, a multi-country outbreak of mpox has been registered in non-endemic regions. After a decrease in the number of confirmed cases in 2023, a re-emerging spread of mpox clade I in Africa and various EU/EEA countries has been registered since mid-2024, and into 2025. According to available genomic data, nonsense or frameshift mutations of MPXV resulting in loss of protein-coding genes and noncoding genes or regulatory regions observed in endemic regions of Central Africa have been associated with human-to-human transmission of the virus. Urbanization caused by population growth in West Africa may increase the risk of human MPXV infection. The infection spread, especially among the countries of the European continent, has led to increased research on mpox prevention and therapy, with data being continuously updated. Monitoring of potential animal reservoirs and exploring new transmission routes are important. Over time, the MPXV has evolved by accumulating genome mutations, contributing to its adaptability and easier human-to-human transmission.